Asserting Turkey in Bosnia : Turkish foreign policy and pro-Turkish activism in Bosnia : actors, discourses and textual corpora (2002-2014) - Mujadžević, Dino, 1977- (Interdisziplinäre Studien zum östlichen Europa, 2017)
The primary goal of this book is to analyze Turkish foreign policy towards Bosnia and Herzegovina under the AKP to as well as the networks of Turkish and local actors in Bosnia that support it. The author looks into how the discourses and actors that emerged in this framework - both in Turkey and as part of Bosnian pro-Turkish activism - interact and respond to each other, and how they have been adapting to the local challenges. Also, Turkish foreign policy under the AKP and its allies in Bosnia is approached as being part of the phenomena related to mainstream Islamic conservativism in both countries. The period selected (2002-2014) represents a chronological section identified by the AKP rule, which most researchers see as an era of the dominance of so-called Neo-Ottomanism in Turkish official and non-official foreign policies towards the Balkans. Asserting Turkey in Bosnia assesses the influence of Turkish foreign policy on Bosnian Muslims, especially among Islamic conservatives, as well as regional reactions to these processes. The focus of this book is on the study of textual sources, including digitized ones. Interpretative analyses in the book rely on the theoretical framework of the Critical Discourse Analysis, which will be implemented through pure qualitative methods as well as the corpus method, a synergy between qualitative and empirical-quantitative approaches.--description from Amazon.